Factors associated with sexual intention towards pre-marital sex activity among school-going late adolescents in Kuantan, Pahang - Abdullah, Fa’iza; Zainuddin, Nur Akmanidar; Draman, Samsul; A. Rahman, Nor Azlina; Muhammad, Noor Azimah (Academy of Family Physicians of Malaysia, 2019)
Background: The consequences of adolescents in early involvement with sexual activity include sexually transmitted diseases, unwanted pregnancy, and unsafe abortion. Objectives: To identify the socio-demographic and sociocognitive factors (permissive attitude, social norms, and selfefficacy) associated with sexual intention to engage in premarital sex among school-going late adolescent in Kuantan, Pahang. Methods: This cross-sectional study was conducted in nine government secondary schools in Kuantan district between February-April 2018. A total of 466 self-administered validated Youth Sexual Intention Questionnaires (YSI-Q) data are collected among unmarried students aged 18-19 years-old. Statistical analyses were done using IBM SPSS version 22.0. Results: Majority of the participants were females (64.4%), Muslims (68.2%) and Malays (67.4%). Simple logistic regression on socio-cognitive factors showed for every one unit increase in permissive attitude, social norms and self-efficacy scores, there were 1.424, 1.303 and 1.215 times increase risk of having sexual intention, with p-value of 0.001 each and 95% CI of odds ratio(OR) 1.268-1.600, 1.191-1.425 and 1.0661.386, respectively. Multivariate logistic regression showed that female had lower risk of having sexual intention compared to male (p=0.001, OR=0.163, CI=0.058-0.462), Non-Malays had higher risk compared to Malay students and ever-smokers had higher risk compared to non-smoker students towards having sexual intention with p=0.001, OR=5.110, CI=1.881-13.886 and p=0.019, OR=3.288, CI=1.218-8.875, respectively. In addition, for every unit increase in permissive attitude score, there was 1.236 times increase risk of having sexual intention with p=0.002 and 95% CI of OR=1.084-1.410. Conclusion: The risk of having sexual intention was found to be higher among males, non-Malay and ever-smoker students; and also among those with higher permissive attitude scores. Therefore, further study and peer education intervention programs are required for school-going students to improve their permissive attitude and to prevent risk behavior that may lead to sexual intention towards pre-marital sex activity.